Transient complete remission of metastasized Merkel cell carcinoma by high-dose polychemotherapy and autologous peripheral blood stem cell transplantation - Waldmann, Volker; Goldschmidt, Hartmut; Jäckel, Andreas; Deichmann, Martin; Hegenbart, Ute; Hartschuh, Wolfgang; Ho, Anthony Dick; Näher, Helmut (British journal of dermatology, 2000)
Merkel cell carcinoma (MCC) is a rare cutaneous tumour with neuroendocrine differentiation. Metastasis occurs preferentially to regional lymph nodes but distant and multiple visceral metastases may occur. Chemotherapy has been performed with a variety of protocols based largely on agents active in small-cell lung cancer. Owing to the rarity of MCC, there is no standard protocol for the treatment of metastatic disease. We report a 59-year-old patient with systemic metastatic MCC. After diagnosis of distant metastases, first-line polychemotherapy (cisplatin 80 mg m−2, doxorubicin 50 mg m−2, etoposide 300 mg m−2 and bleomycin 30 mg) was administered four times at 3-weekly intervals and resulted in partial remission of metastases. Subsequently, high-dose chemotherapy according to the PEI regimen (ifosfamide 12 g m−2, carboplatin 900 mg m−2 and etoposide 1500 mg m−2) was applied, followed by autologous blood stem cell transplantation (ABSCT). This protocol resulted in a complete remission that lasted for 6 months. This is the first report on a complete remission of metastatic MCC after high-dose polychemotherapy and ABSCT. High-dose chemotherapy might be a therapeutic option in chemosensitive metastatic MCC, and further evaluation is warranted.
Elektronische Reproduktion der Druckausgabe
Gesehen am 01.03.2022